Molecules mixture model to explain the nature of interstellar matter - Karim, Layth; Hyder, Nadhem; Al-Baqir, Haydar (Iraqi Journal of Science, 2023)
The nature of interstellar matter has been explained by presenting a model consists of organic and inorganic materials mixture in the wavelength range (9-12) μm.Laboratory samples of different concentrations of these materials were prepared and examined by using FTIR spectrometer device. Results of spectra for these samples are compared with observation of Trapezium nebula in the same wavelengths range. The best mixture model found to fit with observation is a sample consists of:11.96 % (Diatom silica (98% pure silica)) + 14.35 % (Carbon (C)) +27.63 % (Tryptophan amino acid) + 46.06 % (Tyrosine amino acid), this are done using convolution technique. Interstellar matter could be explained biologically, as the contribution of organic material is almost 88